Impacts of low frequency noise exposure on well-being: A case-study from Portugal - Alves, J. A. (2018)
The aim of this article is to assess the impacts of low frequency noise, emitted by high-voltage lines and power poles, on the perception of discomfort, comparing two different groups of inhabitants (exposed and unexposed groups) in two areas in the Northwest of Portugal. It proposes a new oriented methodology to assess discomfort due to the low frequency noise. Materials and Methods: Two predominantly urban areas were used to test the methodology: an ?exposed? area with a high presence of the source under study and an ?unexposed? area without records of power transmission lines. The research developed included measuring sound levels (in frequency bands from 10 to 160 Hz) with the help of a sound level meter in the two selected urban areas. Results: The real sound coming from the source was recorded and reproduced in an audiometric testing booth to determine the hearing threshold and discomfort of the volunteers. Using the criteria curve developed by DEFRA (Department for Environment, Food & Rural Affairs/University of Salford) in 2011, the results reveal that the sound levels recorded for the ?exposed? group were higher than that for the ?unexposed? group. The first recording showed an average of 68.9 dB and the second 64.6 dB, resulting in a significant difference of 4.3 dB between the two groups. After an attempt to isolate the source, the difference was 5.6 dB. Regarding the adapted audiometric tests, the real sound was used, which was collected 5mbetween the receiver and the source. Conclusion: These results provide support that at this distance the noise was considered annoying.